The Biblical concept of Messianism and Messianism in Southern Africa - Martin, Marie-Louise (Morija Sesuto Book Depot, 1964)
Parts 1 and 2, biblical; part 3, pp. 89-187, on messianism in Africa, especially Southern Africa; a theological treatment, which includes Xhosa and Tswanan prophets, Witbooi, Mgijima, Shembe, Lekganyane, Zionism and a typology of messianism.
free
Keywords: Bibel; Bibelwissenschaft; Bible Criticism; Messiah Biblical teaching; Messianisme; Messianismus; Messie Enseignement biblique; Nativistic movements; Nativistic movements South Africa; South Africa